Contribuições do projeto ProMEA na rede (São Carlos SP) à construção de identidade e à formação ambiental continuada de professoras do ensino básico - Tullio, Ariane Di (2014)
This research was linked to the ProMEA Network project: an alternative to overcome some difficulties of environmental education (EE) in primary education. One of its methodological strategies consisted in selecting teachers to articulate municipal schools and the community in EE actions. Thus, a working group was formed/created, consisting of basic education teachers, educational managers / supervisors and this work´s author in the development of her doctoral research. We understand that the way it was designed and developed, especially with regard to reflection and dialogue on the practices among all participants, ProMEA Network also meant a process of formation of environmental educators imbedded in the scope of their activity. The objective of this research was to understand the ways in which a process of EE in a public school can contribute to the formation and construction of the identities of teachers as environmental educators. We also sought to understand the contributions of some specific aspects of the project: the environmental mappings and diagnosis and the watershed approach. The research project was approved by the Ethics Committee on Human Research of UFSCar (Decision 09/2012). The theoretical framework was the philosophical hermeneutics of Hans-Georg Gadamer and the dialogic pedagogy of Paulo Freire, according to which, we assume an intersubjective epistemology, in which knowledge is constructed on dialogue between the subjects about their experiences. Methods and techniques that allow dialogue between the subject and the interpretation of their language were used. The main trajectories of approximation of basic school teachers to EE have been the specialization and / or extension courses and the introduction of EE in their teaching practices. It is also important to emphasize the role of personal experiences and interpersonal relations that acquire new meanings in this process. The acting of environmental educators in the formal education needs to have an institutionalization that values EE in school and facilitates their work within the current structure. The dialogical and critical perspective of EE was highly valued because cooperation, dialogue and reflection among teachers about their practices and their role in school and in society as a whole were mentioned as important aspects in a formative environmental process. This process also needs to produce joy and satisfaction in school life, which favors changes in the professional and personal educators practices. From their EE practice, teachers build an ecological identity, notwithstanding heterogeneous and provisional, depending on opportunities for action, leading them to identify with the environmental ideals not only in the professional context, but also taking these ideas and practices for their personal daily lives. Therefore, in the school context, EE becomes a pathway to the environmental field, and the institutionalization of EE in basic education is essential for the continuity of the construction of this identity by the teachers and consequently environmental educational activities.